Reassessing Ricœur’s Contribution to Inter-religious Dialogue amidst Contemporary Critiques of Religion - Marianne Moyaert (Approaching Religion)
This article critically examines Paul Ricœur’s philosophical contributions to inter-religious dialogue, focusing on his treatment of religion as a presumed universal category. Ricœur’s insights into religious violence and post-religious faith have influenced scholars advocating non-violent interfaith interactions. However, this article argues that Ricœur’s framework, rooted in a modern Western understanding of religion, neglects critical perspectives from scholars in critical religion studies. These perspectives reveal how the category of religion is historically contingent, Eurocentric, and intertwined with processes of power and exclusion. By uncritically adopting this concept, Ricœur’s approach risks perpetuating hierarchical structures that marginalize non-Western religious traditions and obscure histories of violence against religious minorities.